Genome profiling of vancomycin-resistant entercoccal clinical isolates from Lebanon. (c2019) - Panossian, Balig V. (2019)
Vancomycin resistant enterococci (VRE) are a considerable burden on treatment, and infection and transmission control. Studying the intricacies on the wholegenome single nucleotide level is more informative than routine phenotypic analysis. In this study, 21 clinical isolates of enterococci were first identified by MALDI-TOF, and disk diffusion and E-test were used to determine antimicrobial susceptibility profiles. Whole-genome sequencing (WGS) was conducted using Illumina MiSeq platform. Resistance genes, ST-types, wgSNPs, cgSNPs, pangenomes of coding and non-coding regions, as well as recombination hotspots were evaluated for all the isolates using different bioinformatic approaches. The VRE isolates clustered under two main ST types (ST80, ST203) with some isolates having very similar whole-genome average nucleotide identities (wgANI). Pan genome analysis revealed that the isolates were much more unique in their protein coding sequences and showed pronounced heterogeneity as a population. A closer look at the resistance determinants, in particular, the vancomycin resistance genes flanked by transposon fragments and recombination loci, revealed uniquely evolved features that emphasized the polyclonal spread of these pathogens. The vancomycinsusceptible isolates also showed unique genomic features some of which had closely related genomic profiles as that of the vancomycin-resistant clones of similar ST types. A notable case was EF6 (vancomycin-susceptible), which was almost identical (99.91% average nucleotide identity) to EF15 (vancomycin resistant) except for the vancomycin resistance cassette. A few isolates were too diverse for batched intergenomic comparative analyses, and one isolate harbored additional antibiotic resistance determinants uncommon in the other enterococci. This study provided the first insights on the genomic diversity of vancomycinresistant enterococci circulating in Lebanon. Our results demonstrated how an endto- end whole-genome sequence-based outbreak surveillance, and resistance profiling scheme could help in differentiating between closely related VRE isolates, whereas phenotypic or even classical molecular approaches fail to highlight these complexities.